2016
DOI: 10.14238/sp17.3.2015.216-21
|View full text |Cite
|
Sign up to set email alerts
|

Faktor yang Memengaruhi Kadar NT-proBNP pada Anak dengan PJB Pirau Kiri ke Kanan yang Mengalami Gagal Jantung

Abstract: Latar belakang. Amino terminal pro-brain natriuretic peptide (NT-proBNP) merupakan neurohormon jantung yang dikeluarkansebagai respon terhadap beban tekanan dan volume yang berlebihan pada gagal jantung. Secara teori, faktor yang memengaruhikadar NT-proBNP di antaranya anemia, frekuensi ISPA sering, dan diameter defek besar.Tujuan. Membuktikan bahwa anemia, frekuensi ISPA sering, dan diameter defek besar sebagai faktor yang dapat memengaruhikadar NT-proBNP pada anak dengan PJB pirau kiri ke kanan yang mengalam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…A 1 g/dL decrease in haemoglobin levels can also increase NT-proBNP levels by 20%. 38 The results of this study showed a significant correlation with the level of weak strength between ferritin levels and NT-ProBNP levels in thalassemia patients at Dr. M. Djamil Padang Hospital (r = 0.399, p = 0.039). These results are in line with the research of Singh et al, which showed a significant correlation between serum NT-proBNP and ferritin levels in thalassemia patients (r = 0.306, p = 0.006).…”
Section: Discussionmentioning
confidence: 57%
“…A 1 g/dL decrease in haemoglobin levels can also increase NT-proBNP levels by 20%. 38 The results of this study showed a significant correlation with the level of weak strength between ferritin levels and NT-ProBNP levels in thalassemia patients at Dr. M. Djamil Padang Hospital (r = 0.399, p = 0.039). These results are in line with the research of Singh et al, which showed a significant correlation between serum NT-proBNP and ferritin levels in thalassemia patients (r = 0.306, p = 0.006).…”
Section: Discussionmentioning
confidence: 57%
“…One of the symptoms experienced by patients with heart failure and of course the NT-ProBNP is increased. If we look further, this relationship can lead to kidney failure, where the association between heart and kidney failures is quite significant in the presence of anemia [2]. Patients with hypovolemia had the lower NT-proBNP values than patients with euvolemia [7].…”
Section: Resultsmentioning
confidence: 99%
“…NT-proBNP increases due to anemia every 1 g/dL decrease in hemoglobin, and is useful for the diagnosis of heart failure in addition to echocardiography. Furthermore, the acute respiratory infections are also associated with an increase in NT-proBNP [2]. NT-proBNP also helps diagnose heart failure in acute dyspnoe [3].…”
Section: Introductionmentioning
confidence: 99%